Sequence variations within the genes related to hemostatic imbalance and their impact on coronary artery disease in Turkish population - TOKSOY ÖNER, EBRU (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Coronary artery disease (CAD) is reported to be associated with some genetic risk factors. Since identification of genetic risk factors for CAD in different ethnic groups is important for the development of new intervention and prevention programs, we investigated the association between the R353Q and -323ins10 polymorphisms in Factor VII gene, C677T mutation in MTHFR, Factor V Leiden and PT G20210A mutations and CAD in Turkish population. The promoter region of the PAI-1 gene was also screened by SSCA (single-stranded conformation analysis) using specifically designed primers. 137 CAD patients with early onset documented by coronary angiography and 41 individuals who had no significant coronary stenosis by angiography as control group were screened for the identification of the polymorphisms. In conclusion, Factor V Leiden was found to be an independent genetic risk factor for CAD in Turkish population. Combined risk assessment indicated that the coexistence of two other inherited thrombophilia markers, namely MTHFR C677T and PT G20210A with Factor V Leiden may increase the risk of the development of the disease in this population. The results of the present study show that there is no statistically significant association between the two polymorphisms in Factor VII gene, MTHFR C677T polymorphism, PT G20210A polymorphism, 4G/5G polymorphism of PAI-1 and CAD in Turkish population. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: polymorphisms; coagulation factors; thrombosis; coronary artery disease; PLASMINOGEN-ACTIVATOR INHIBITOR-1; FACTOR-V-LEIDEN; FACTOR-VII GENE; METHYLENETETRAHYDROFOLATE REDUCTASE MTHFR; FAMILIAL MYOCARDIAL-INFARCTION; VENOUS THROMBOSIS; PROTHROMBIN GENE; HEART-DISEASE; RISK FACTOR; PAI-1 GENE